Novel Growth Hormone Receptor Gene Mutation in a Patient with Laron Syndrome - Arman, Ahmet; Yüksel, Bilgin; Çoker, Ajda; Sarıöz, Özlem; Temiz, Fatih; Topaloğlu, Ali Kemal (Freund Publishing House Ltd, Po Box 35010, Tel Aviv 61350, israel, 2010)
Growth Hormone (GH) is a 22 kDa protein that has effects on growth and glucose and fat metabolisms. These effects are initiated by binding of growth hormone (GH) to growth hormone receptors (GHR) expressed in target cells. Mutations or deletions in the growth hormone receptor cause an autosomal disorder called Laron-type dwarfism (LS) characterized by high circulating levels of serum GH and low levels of insulin like growth factor-1 (IGF-1). We analyzed the GHR gene for genetic defect in seven patients identified as Laron type dwarfism. We identified two missense mutations (S40L and W104R), and four polymorphisms (S473S, L526I, G168G and exon 3 deletion). We are reporting a mutation (W104R) at exon 5 of GHR gene that is not previously reported, and it is a novel mutation.
Keywords: Growth Failure; Laron Syndrome; Growth Hormone Receptor; İnsensitivity Syndrome; Pituitary Dwarfism; Binding-Protein; Deletion; Büyüme Geriliği; Laron Sendromu; Büyüme Hormonu Reseptörü; Duyarsızlık Sendromu; Hipofiz Cücelik; Bağlayıcı Protein